2016
DOI: 10.1016/j.resuscitation.2015.09.399
|View full text |Cite
|
Sign up to set email alerts
|

Billing diagnoses do not accurately identify out-of-hospital cardiac arrest patients: An analysis of a regional healthcare system

Abstract: Background International Classification of Diseases 9th Edition’s Clinical Modification (ICD-9CM) codes are frequently used in health services research. We tested the operating characteristics of ICD-9CM codes for identifying out-of-hospital cardiac arrest (OHCA) subjects. Methods We used ICD-9CM codes to generate an “administrative cohort” of subjects treated after possible OHCA at one of six emergency departments (EDs) between January 2010 and April 2014. We performed a structured chart review to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…For patients identified by ICD-9CM code, we confirmed the diagnosis of SCA with a structured chart review, which we have confirmed to be essential for accurate case ascertainment. [23] We included patients resuscitated from in-hospital or out-of-hospital SCA who survived to hospital discharge, and excluded those with SCA secondary to surgical etiology such as trauma, or neurological catastrophe. We extracted name, sex, date of birth, race, marital status, state of last known residence, and social security number, and used these data to query the National Death Index (NDI) 2013 NDI Final File to obtain long-term survival data.…”
Section: Methodsmentioning
confidence: 99%
“…For patients identified by ICD-9CM code, we confirmed the diagnosis of SCA with a structured chart review, which we have confirmed to be essential for accurate case ascertainment. [23] We included patients resuscitated from in-hospital or out-of-hospital SCA who survived to hospital discharge, and excluded those with SCA secondary to surgical etiology such as trauma, or neurological catastrophe. We extracted name, sex, date of birth, race, marital status, state of last known residence, and social security number, and used these data to query the National Death Index (NDI) 2013 NDI Final File to obtain long-term survival data.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study called into question the utility of administrative data for identifying out-of-hospital CA. [ 51 ] Investigators queried ICD-9 codes for cardiac arrest as well as VF, paroxysmal ventricular tachycardia, ventricular flutter, and respiratory arrest and found that only 40% of patients who had these ICD-9 codes had an out-of-hospital CA upon chart review. However, 94% of the CAs in our registry matched to administrative data, although there were some significant differences between the patients who were matched and those who were not.…”
Section: Discussionmentioning
confidence: 99%
“…First, the data was obtained from an administrative database, which has been shown in the past to have inaccuracies when used for cardiac arrest research. (40) To overcome this, procedures and drugs administrated during resuscitation were another key element in data selection in addition to ICD-9 diagnosis code. Only those with attempts in resuscitation were enrolled in the analysis.…”
Section: Discussionmentioning
confidence: 99%